The Two Cultures: The place of humanities research in leadership studies. (August 2019) - Ciulla, Joanne B
This article explains why leadership is a natural part of the humanities. It compares and contrasts the research methods and types of knowledge that we get from the humanities with those of the social sciences. I argue that the humanities offer, what is in some ways, a better foundation for leadership research and that without them, we will never really understand leadership.